O processo de formação da estratégia de manufatura em empresas brasileiras de médio e pequeno porte - Correa, Carlos Alberto (2008)
The research reported here deals with the process of manufacturing strategy formation in small and medium sized Brazilian companies. Making use of an extensive literature review, an analytical tool is developed to help classify and analyze the manufacturing strategy formation processes, which utilizes two main dimensions: the predominant direction (top down or bottom up) and the consideration (or not) of trade-offs between manufacturing performance criteria in the formation of manufacturing strategy. This analytical tool is then applied in the in-depth analyses of four case studies of Brazilian mid-sized manufacturers. Conclusions are drawn and hypotheses formulated as to how Brazilian small and medium sized companies form their manufacturing strategies. Also based on the case studies findings and on the literature review, 10 requisites are identified as desirable to be present in an ideal process of manufacturing strategy formation in small and mid-sized Brazilian companies. Based on these 10 requisites and with the objective of orienting practitioners, a step-by-step process is developed and presented so that Brazilian companies and their executives can better manage their manufacturing strategy formation process, and by doing so, benefit from the state of the art of the conceptual developments in the field.